Angiotensin-(1–7) Administration Reduces Oxidative Stress in Diabetic Bone Marrow - Mordwinkin, N. M. (Endocrine Society, 2012)
Diabetics have an increased risk of developing cardiovascular disease, in part due to oxidative stress, resulting in endothelial nitric oxide synthase (eNOS) dysfunction. Studies have demonstrated that angiotensin-(1–7) [Ang-(1–7)] can activate eNOS activity. Because the bone marrow is a primary source of a number of progenitors important in physiological homeostasis and healing, the goal of this study was to evaluate the in vivo effects of Ang-(1–7) treatment on oxidative stress and the ensuing nitrative stress in diabetic bone marrow and its potential pathways. BKS.Cg-Dock7(m) +/+ Lepr(db)/J mice and their heterozygous controls were administered Ang-(1–7) alone or combined with A-779, losartan, PD123,319, nitro-l-arginine methyl ester, or icatibant sc for 14 d. The bone marrow was then collected to measure nitric oxide levels, eNOS phosphorylation, and expression of nitric oxide synthase, superoxide dismutase, and p22-phox. Nitric oxide levels in the bone marrow were significantly decreased in diabetic mice, and Ang-(1–7) treatment was able to significantly increase these measures (P < 0.01). This effect was blocked by the coadministration of PD123,319, A-779, nitro-l-arginine methyl ester, and icatibant. In addition, Ang-(1–7) treatment reversed the paradoxical increase in eNOS and neuronal nitric oxide synthase expression and decreased the phosphorylation of eNOS at Thr495 seen in diabetic mice. Ang-(1–7) also reversed diabetes-induced production of reactive oxygen species by decreasing p22-phox expression and increasing superoxide dismutase 3 expression, leading to a significant reduction in 3-nitrotyrosine formation in diabetic bone marrow (P < 0.05). Our findings demonstrate that Ang-(1–7) administration decreases diabetes-induced oxidative stress in the bone marrow and modifies pathways involved in eNOS dysfunction.